2020
DOI: 10.1002/hep.31116
|View full text |Cite
|
Sign up to set email alerts
|

c‐Jun NH2‐Terminal Protein Kinase Phosphorylates the Nrf2‐ECH Homology 6 Domain of Nuclear Factor Erythroid 2–Related Factor 2 and Downregulates Cytoprotective Genes in Acetaminophen‐Induced Liver Injury in Mice

Abstract: BaCKgRoUND aND aIMS: Acetaminophen (APAP) overdose induces severe liver injury and hepatic failure. While the activation of c-Jun NH 2 -terminal kinase ( JNK) has been implicated as a mechanism in APAP-induced liver injury, the hepatic defense system controlled by nuclear factor erythroid 2-related factor 2 (Nrf2) plays a central role in the mitigation of APAP toxicity. However, the link between the two signaling pathways in APAP-induced liver injury (AILI) remains unclear. appRoaCH aND ReSUltS: In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…This interaction allows the phosphorylation of Ser residues at Neh6 degron domain of NRF2. Thus, it was demonstrated that p-JNK phosphorylates Ser335 at DSGIS motif of NRF2, codifying its degradation through a KEAP1-independent mechanism [249].…”
Section: Miscellaneous Pathways Regulating the Post-translational Phomentioning
confidence: 99%
“…This interaction allows the phosphorylation of Ser residues at Neh6 degron domain of NRF2. Thus, it was demonstrated that p-JNK phosphorylates Ser335 at DSGIS motif of NRF2, codifying its degradation through a KEAP1-independent mechanism [249].…”
Section: Miscellaneous Pathways Regulating the Post-translational Phomentioning
confidence: 99%
“…Furthermore, fullerenol C 60 (OH) 24 is involved in phosphorylation and activation of p38 mitogen-activated protein kinase (MAPK) kinase, and then the kinases, which are regulated by extracellular signals, as well as c-Jun-N-terminal kinases [ 135 ]. All mentioned kinases phosphorylate Nrf2 and enable its translocation into the cell nucleus [ 163 , 164 ].…”
Section: Biological Effects Of Carbon Nanomaterialsmentioning
confidence: 99%
“…First, our findings of the phosphorylation of nuclear erythroid 2 p45‐related factor 2 (Nrf2) and diminished mRNAs of NAD(P)H:quinone oxidoreductase 1 (Nqo1) , glutathione S‐transferase A3 ( Gstα3 ), glutathione S‐transferase M1 ( Gstm1 ), glutathione S‐transferase M5 ( Gstm5 ), and aldo‐keto reductase 1C ( AKR1C ) by 6 hours after acetaminophen (APAP) treatment (300 mg/kg) (Supporting Fig. S2B), ( 1 ) indicate that the Nrf2/Antioxidant responsive element (ARE) cytoprotective system is impaired from a very early time point. No significant changes in the protein levels were detected at the 6‐hour time point.…”
mentioning
confidence: 99%